2011
DOI: 10.1007/dcr.0b013e3182028576
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up After an Initial Episode of Diverticulitis: What Are the Predictors of Recurrence?

Abstract: Although diverticulitis recurrence is common following an initial attack that has been managed medically, complicated recurrence is uncommon. Patients who present with a family history of diverticulitis, long segment of involved colon, and/or retroperitoneal abscess are at higher risk for recurrent disease. Patients who present with right-sided diverticulitis are at low risk for recurrent disease. These findings should be taken into consideration when counseling patients regarding the potential benefits of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
2
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 20 publications
2
127
2
19
Order By: Relevance
“…Of those patients, about 85% will have uncomplicated disease [5]. Furthermore, recurrence occurs in about 13.3-23.4% of people with diverticulitis [6][7][8][9]. This is in contrast to earlier studies that estimated a recurrence rate of about 25-45% [10][11][12].…”
Section: Introductioncontrasting
confidence: 52%
“…Of those patients, about 85% will have uncomplicated disease [5]. Furthermore, recurrence occurs in about 13.3-23.4% of people with diverticulitis [6][7][8][9]. This is in contrast to earlier studies that estimated a recurrence rate of about 25-45% [10][11][12].…”
Section: Introductioncontrasting
confidence: 52%
“…After successful medical treatment of the acute episode, patients with severe diverticulitis on CT had a statistically greater incidence of secondary bad outcome than patients with moderate diverticulitis (36 vs. 17 %) [142,143]. Hall [144] showed in a multivariate analysis of 672 patents that left-sided AD, length of involved colon [5 cm and a retroperitoneal abscess were predictors for recurrence. However, the study could not report a multivariate model for complicated recurrence because of the small number of events.…”
Section: What Are the Actual Indications For Elective Surgery?mentioning
confidence: 99%
“…8 More recently, a 5-year recurrence of 36% (95% CI, 31.4-40.6%) was reported in a retrospective study of 672 patients admitted with acute diverticulitis. 9 Of 221 patients treated medically following a first admission with acute diverticulitis, overall readmission was 20.8% (46/221). 10 A further study of 502 patients from New Zealand reported a recurrence rate of 18.8% (60/320) with a median follow-up of 101 months and no increase in mortality related to recurrent episodes.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%